2013
DOI: 10.1002/star.201300124
|View full text |Cite
|
Sign up to set email alerts
|

Effect of water requirement and alkali on wheat–rice noodle quality

Abstract: High protein wheat flour (14.8% protein) was diluted with high AM rice flour to obtain a noodle quality that was comparable to all‐purpose wheat flour of 10.6% protein content. Rice flour substitution levels and water addition levels were studied in an attempt to optimize noodle quality using response surface methodology (RSM). Increased substitution of wheat flour with rice flour and increasing water addition levels resulted in the lowering of all textural parameters; maximum tensile strength, maximum distanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Remarkedly, the higher L* value and the lower b* and a* value were perceived for RD43 rice noodles, suggesting that incorporation of RD43 rice flour made the noodle brighter with a slightly lower yellowness and redness (Table 9). The findings are agreed with the results of Suwannaporn et al (2014) who reported that the replacement of wheat flour by rice flour decreased yellowness and redness with a concomitant increase in lightness of noodles. There are many factors affecting the quality of Asian noodles such as raw materials and food processing.…”
Section: Resultssupporting
confidence: 92%
“…Remarkedly, the higher L* value and the lower b* and a* value were perceived for RD43 rice noodles, suggesting that incorporation of RD43 rice flour made the noodle brighter with a slightly lower yellowness and redness (Table 9). The findings are agreed with the results of Suwannaporn et al (2014) who reported that the replacement of wheat flour by rice flour decreased yellowness and redness with a concomitant increase in lightness of noodles. There are many factors affecting the quality of Asian noodles such as raw materials and food processing.…”
Section: Resultssupporting
confidence: 92%
“…However, the gluten network of M3 was more pronounced than that of M1 and M2 during kneading. This is due to the increasing amount of water addition in M1, M2 and M3 (31.6%, 35.4% and 39.1%, respectively), which promotes the hydration and extension of the gluten network (Suwannaporn et al ., 2014). Otherwise, starch granules are considered as fillers in the proteinaceous gluten; the BS with higher adhesion (relative to AS) can be packed tightly by the gluten network, which can be observed in SEM images (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Kruger et al ( 12 ) and Shiauet et al ( 13 ) reported that the cutting force and tensile strength of extruded noodles increased after adding “Kansui” or a mixture of sodium carbonate and potassium carbonate. Suwannaporn et al ( 14 ) reported that the addition of appropriate amounts of potassium carbonate improved the viscosity, toughness and sensory qualities of noodles. Tao et al ( 15 ) reported that the addition of appropriate amounts of sodium carbonate improved the gluten network and had a significant impact on dough structure, and these changes made the cooking loss and rehydration greater of alkaline noodles.…”
Section: Introductionmentioning
confidence: 99%